Plasmon-enhanced fluorescence for biophotonics and bio-analytical applications - Dasgupta, Souradip; Ray, Krishanu (Frontiers in Chemistry, 2024)
Fluorescence spectroscopy serves as an ultrasensitive sophisticated tool where background noises which serve as a major impediment to the detection of the desired signals can be safely avoided for detections down to the single-molecule levels. One such way of bypassing background noise is plasmon-enhanced fluorescence (PEF), where the interactions of fluorophores at the surface of metals or plasmonic nanoparticles are probed. The underlying condition is a significant spectral overlap between the localized surface plasmon resonance (LSPR) of the nanoparticle and the absorption or emission spectra of the fluorophore. The rationale being the coupling of the excited state of the fluorophore with the localized surface plasmon leads to an augmented emission, owing to local field enhancement. It is manifested in enhanced quantum yields concurrent with a decrease in fluorescence lifetimes, owing to an increase in radiative rate constants. This improvement in detection provided by PEF allows a significant scope of expansion in the domain of weakly emitting fluorophores which otherwise would have remained unperceivable. The concept of coupling of weak emitters with plasmons can bypass the problems of photobleaching, opening up avenues of imaging with significantly higher sensitivity and improved resolution. Furthermore, amplification of the emission signal by the coupling of free electrons of the metal nanoparticles with the electrons of the fluorophore provides ample opportunities for achieving lower detection limits that are involved in biological imaging and molecular sensing. One avenue that has attracted significant attraction in the last few years is the fast, label-free detection of bio-analytes under physiological conditions using plasmonic nanoparticles for point-of-care analysis. This review focusses on the applications of plasmonic nanomaterials in the field of biosensing, imaging with a brief introduction on the different aspects of LSPR and fabrication techniques.